The Defence of Duffer's Drift : A Few Experiences in the Field Defence for Detached Posts Which May Prove Useful in Our Next War - Swinton, Ernest Maj. Gen., 1868-1951 (Oxford George Ronald, 1977)
"Duffer's Drift" is a classic text on training young officers, derived from tactics employed in the Boer War, which is thought-provoking and entertaining, in contrast to the unimaginative rote-learning of the drill books and "Field Exercises" which had previously passed for training.
Keywords: South African War (1899-1902) -- Tactics -- Guerrilla warfare